2014
DOI: 10.1007/s00415-014-7528-z
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided cognitive rehabilitation improves cognitive performances and induces brain functional connectivity changes in relapsing remitting multiple sclerosis patients: an exploratory study

Abstract: To better understand the effects of short-term computer-based cognitive rehabilitation (cCR) on cognitive performances and default mode network (DMN) intrinsic functional connectivity (FC) in cognitively impaired relapsing remitting (RR) multiple sclerosis (MS) patients. Eighteen cognitively impaired RRMS patients underwent neuropsychological evaluation by the Rao's brief repeatable battery and resting-state functional magnetic resonance imaging to evaluate FC of the DMN before and after a short-term (8 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 58 publications
7
86
0
Order By: Relevance
“…In line with these findings, a crucial role of the inferior parietal lobule in working memory and sustained attention tasks, such as the PVSAT, was observed in a recent meta-analysis conducted on both healthy controls and PwMS (Kollndorfer et al 2013). The inferior parietal lobule has been demonstrated to be more active during the 2-back task in PwMS with preserved cognition compared to those with cognitive deficits (Rocca et al 2010) and to present increased functional connectivity with the default mode network after cognitive rehabilitation (Bonavita et al 2015). Moreover, a resting-state investigation involving PwMS showed increased functional connectivity of the right inferior parietal lobule after cognitive treatment (Parisi et al 2014).…”
Section: Discussionsupporting
confidence: 57%
“…In line with these findings, a crucial role of the inferior parietal lobule in working memory and sustained attention tasks, such as the PVSAT, was observed in a recent meta-analysis conducted on both healthy controls and PwMS (Kollndorfer et al 2013). The inferior parietal lobule has been demonstrated to be more active during the 2-back task in PwMS with preserved cognition compared to those with cognitive deficits (Rocca et al 2010) and to present increased functional connectivity with the default mode network after cognitive rehabilitation (Bonavita et al 2015). Moreover, a resting-state investigation involving PwMS showed increased functional connectivity of the right inferior parietal lobule after cognitive treatment (Parisi et al 2014).…”
Section: Discussionsupporting
confidence: 57%
“…CR protocols designed to train multiple cognitive skills, including PS, have also been developed and tested (2124), with improved cognitive performance noted following treatment. For example, improvement has been shown in PS and other targeted cognitive domains following RehaCom, which persist over time [e.g., (25)].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, RS is particularly suited for patients with impairment in targeted functions, and could be a useful technique to assess changes after neurorehabilitation and symptomatic therapy. Recent studies have reported RS changes in patients with MS following a cognitive rehabilitation program (CRP) . In addition, it has been shown that the rest periods in classical block‐design fMRI studies can be reanalyzed to assess functional connectivity …”
Section: Introductionmentioning
confidence: 99%